The lncRNA PDIA3P Interacts with miR-185-5p to Modulate Oral Squamous Cell Carcinoma Progression by Targeting Cyclin D2 - Cheng-Cao Sun; Ling Zhang; Guang Li; Shu-Jun Li; Zhen-Long Chen; Yun-Feng Fu; Feng-Yun Gong; Tao Bai; Ding-Yu Zhang; Qing-Ming Wu; De-Jia Li (Elsevier, 2017)
Long noncoding RNAs (lncRNAs) are emerging as important regulators during tumorigenesis by serving as competing endogenous RNAs (ceRNAs). In this study, the qRT-PCR results indicated that the lncRNA protein disulfide isomerase family A member 3 pseudogene 1 (PDIA3P) was overexpressed in oral squamous cell carcinoma (OSCC) and decreased the survival rate of OSCC patients. CCK-8 and clonal colony formation assays were used to detect the effects of PDIA3P on proliferation. Results revealed that silencing PDIA3P by small interfering RNA (siRNA) inhibited OSCC cell proliferation and repressed tumor growth and reduced the expression of proliferation antigen Ki-67 in vivo. Furthermore, the interaction between PDIA3P and miRNAs was then analyzed by qRT-PCR and luciferase reporter gene assay. We found that PDIA3P negatively regulated miR-185-5p in OSCC cells. Simultaneously, we found that silencing PDIA3P by siRNA suppressed proliferation via miR-185-5p in OSCC cells. Moreover, silencing PDIA3P by siRNA inhibited CCND2 protein (no influence on mRNA levels) expression via miR-185-5p in OSCC cells, and CCND2 facilitated cell proliferation of SCC4 and SCC15 cells induced by sh-PDIA3P#1. Therefore, our study demonstrated that PDIA3P may be a therapeutic target for the treatment of OSCC.